Estudio de innovación y nuevas estrategias de marketing del restaurante “SMAC” en el cantón Montalvo - Echeverría Barragán, Nayelhi (2023)
Today, a large part of the population in the world has a business, or the idea of having one, but it is not so easy to start this business, it takes a lot of patience, perseverance and intelligence. Nowadays, marketing has become such an indispensable and relevant tool for a venture or business, since it allows an institution to reach a large number of people and thus obtain profits. Marketing is one of the most fundamental parts of our business. It comes full of countless strategies, which adapts to each business or each company. That is why it is very important to know the true meaning of the word Marketing, to understand how it works. To do this, there are bases from authors such as Philip Kotler, who deals with the importance of marketing from his professional point of view. Together these two concepts come to the conclusion of the importance of this sales tool in an establishment. In this study, some of the general strategies of guided marketing with Restaurant “Smac” in the Montalvo canton of the Province of Los Ríos, will be studied and verified through data collection instruments, immersed in a mixed approach (qualitative and quantitative). With their respective results, through graphs with percentages of survey responses.